Phylogenetics of subfamily murin Ea (Rodentia : Muridae) In Malaysia inferred from mitochondrial and nuclear genes - Nur Aida, Md Tamrin (Universiti Malaysia Sarawak (UNIMAS), 2011)
ITraditionally, taxonomic status of Murinae was based on morphological characteristics. The classification was always outdated due to the variation of morphological traits caused by rapid adaptation towards ecological habitats and high rate of evolution in Murinae. The variation of external features sometimes does not indicate the species to be in distinct taxa, at least not in Genetic Species Concept. As closely related species in the subfamily Murinae are morphologically similar to each other, the taxonomic status of Murinae is poorly resolved up until recent. Many studies have been done using genetic data, morphology, immunology, albumin and karyotypic analyses but the information of Murinae in Malaysia is still lacking)Phylogenetic relationship of Murinae were reviewed in this study inferred by mitochondrial gene (mtDNA) of cytochrome oxidase I (COI) and cytochrome b (cyt b) as well as one nuclear gene (nucDNA) of recombination activating gene (RAG2). The evolutionary, interspecific and intraspecific relationship between selected species in the Murinae and their divergence time were investigated during this study. The phylogenetic trees were reconstructed using four methods for each gene, namely, neighbour joining (NJ), maximum parsimony (MP), maximum-likelihood (ML) and Bayesian methods. From this study, six monophyletic lineages were observed, namely, Rattus, Beiylmys, Maxomys, Sundamys, Leopoldamys and Niviventer. The interrelationship of Murinae was incongruent between the genes analyses and some of the species were unresolved in the groupings. This study also found that there were cryptic species within M. whiteheadi and M. ochraceiventer population with external morphology similar to M. whiteheadi but separated with high genetic divergence whilst closely related by genetic distance to M ochraceiventer. Genetically, two types (Type A and Type B) of M rajah, R. rattus and S. muelleri were also found in this study by observing the phylogenetic trees. NJ and Bayesian methods gave the most resolved topologies. MP and ML methods might give better resolution if more data were added. Cyt b was observed to be the best gene to study the evolution of Murinae.